Effect of ultrasonic treatment on mechanical behaviour of ferrite-martensite steel; Korus 2004; Vol. 3 - Panin V. E. Viktor Evgenyevich; Panin A. V. Alexey Viktorovich; Pochivalov Yu. I.; Antipin R. A.; Klimenov V. A.; Ovechkin B. B. Boris Borisovich; Slosman A. I.; Son A. A.; Mel'nikova E. A.; Leont'eva-Smirnova M. V. (2004, 2004)
The effect of ultrasonic treatment on the feature of plastic deformation and mechanical properties of ferrite-martensite steel with various structural states were investigated. To change the initial structural states the specimens were subjected to heat hardening, ageing, cold rolling and/or nitration. It is shown that ultrasonic treatment forms within the surface layer submicrocrystalline structure. As a result, the microscale level of deformation is suppressed. Ultrasonic impact of untreated and/or hardened and aged specimens rises the strength of the materials. Deformation of the specimens subjected to cold rolling with subsequent ultrasonic treatment is strongly localised at its ends. It results in drastic reduction of material strength